PENGARUH METODE BELAJAR DEMONSTRASI DAN MINAT BELAJAR SISWA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN KELAS XI DI SMA NEGERI 5 PEMATANGSIANTAR TAHUN PELAJARAN 2024/2025 - Meiliawati Adillah; Sepriandison Saragih; Marthin Fransisco Manihuruk (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine whether there is an influence of demonstration learning methods and student interest in learning on student learning achievement in class XI citizenship education subjects at SMA Negeri 5 Pematangsiantar for the 2024/2025 academic year. The problem in this research is the influence of the demonstration learning method and students' interest in learning on student learning achievement in Class The population and sample in this study were all 44 students in class XI-3 and XI-4. The instruments used are questionnaires and documentation. The quality of research instruments for questionnaires and student learning achievement is assessed through validity and reliability tests. All data from the three variables above were first tested whether they were normally distributed or not using the goodness of fit test or chi square test and it turned out that the three variables were normally distributed. The next step is testing the hypothesis by calculating the linear regression equation, namely Y over X1 and X2 is = 2.11+1.17x1+2.95 The influence coefficient obtained is as follows: (1) The contribution coefficient of Y to X1 is 22.37%% (2) The contribution coefficient of Y to X2 is 59.06% (3) The contribution coefficient of X1 to X2 is 63.45% ( 4) The contribution coefficient of Y to X1 and X2 is 48.29%. Based on the hypothesis test, namely the significant influence test (t test) by rejecting H0 and accepting H1, we obtain: The Influence of Demonstration Learning Methods on Student Learning Achievement in Class XI Citizenship Education Subjects at SMA Negeri 5 Pematangsiantar T.A. 2024/2025 is “very strong” (1.87). The influence of student learning interest on student learning achievement in class XI citizenship education subjects at SMA Negeri 5 Pematangsiantar T.A. 2024/2025 is “strong” (0.9607). The influence between the demonstration learning method and students' interest in learning on students' learning achievement in class XI at SMA Negeri 5 Pematangsiantar for the 2024/2025 academic year is “strong” (0.9915).